2015
DOI: 10.1038/srep11877
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Genetic Dynamics of an Invasive Species, Frankliniella occidentalis (Pergande), in an Early Phase of Establishment

Abstract: Many species can successfully colonize new areas despite their propagules having low genetic variation. We assessed whether the decreased genetic diversity could result in temporal fluctuations of genetic parameters of the new populations of an invasive species, western flower thrips, Frankliniella occidentalis, using mitochondrial and microsatellite markers. This study was conducted in eight localities from four climate regions in China, where F. occidentalis was introduced in the year 2000 and had lower gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
6
20
1
Order By: Relevance
“…The common haplotypes found in this study were similar to those found in previous studies (Yang et al., ), except for haplotype 8, which was common in five populations from Beijing. This haplotype was absent from other Chinese populations (except for one individual from LNCY) or from populations in the native range of WFT that have been characterized (Brunner & Frey, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The common haplotypes found in this study were similar to those found in previous studies (Yang et al., ), except for haplotype 8, which was common in five populations from Beijing. This haplotype was absent from other Chinese populations (except for one individual from LNCY) or from populations in the native range of WFT that have been characterized (Brunner & Frey, ).…”
Section: Discussionsupporting
confidence: 90%
“…The source population for most Beijing populations appears different to the source for other Chinese populations, with a likely secondary introduction into Beijing. The high genetic diversity present at the YNHH site and early record of WFT at this site suggests that WFT from Yunnan served as the source population for other regions (GZGY, XZLS, XJWL, LNCY, and BJYQ) as suggested previously (Yang et al., , ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…9 Since then, F. occidentalis has spread rapidly throughout China to become one of the major pests of vegetable and floriculture crops. 2,10 Although many approaches have been developed for the management of thrips, 11 -13 control efforts against F. occidentalis continue to be heavily reliant on the application of insecticides, especially in virus-sensitive crops.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we cannot reject the possibility that these species naturally extended their habitats northward due to the recent increase in seawater temperature attributable to either global warming or the variations of the path of the warm Kuroshio Current that flows past the Pacific coast of Japan (Ogaki 2010). Newly colonized populations tend to exhibit low levels of genetic variations (e.g., Chuong et al 2008;Yang et al 2015). The haplotype diversity (h: Nei 1987) of our C. angulata and C. dianbaiensis population samples was 0.933 (11 haplotypes) and 0.833 (7 haplotypes), respectively (calculated using DnaSP software version 5.10.01; Librado & Rozas 2009).…”
mentioning
confidence: 99%